PENYELESAIAN KONFLIK DALAM LINGKUNGAN PERUSAHAAN BERDASARKAN ADAB DAN NORMA DALAM PANCASILA - Devra, Desi Devrika (Komunitas Manajemen Kompetitif, 2024)
Conflict resolution within the company environment is an important aspect to maintain the stability and sustainability of organizational operations. This article discusses an approach to conflict resolution based on the customs and norms contained in Pancasila as the basis of the state and guidelines for national life. The method used is qualitative analysis by reviewing Pancasila values, such as divinity, humanity, unity, deliberation and justice, in the context of company dynamics. The research results show that the application of Pancasila values is able to create a harmonious work atmosphere, increase collective awareness, and encourage conflict resolution through deliberation and justice. By prioritizing Pancasila etiquette and norms, companies can build a work culture that is more ethical, inclusive and oriented towards common interests. It is hoped that these findings can serve as a guide for management in managing conflicts constructively in accordance with national values